Considering Restorative Justice in Criminal Cases Involving Indonesian National Armed Forces Personnel - Goeniswara, Dinda; Yitawati, Krista; Chairani, Mierza Aulia (Jurnal Ilmu Hukum Kyadiren, 2026)
This study is motivated by the evolving paradigm in criminal justice, which is no longer solely oriented toward punishment but increasingly emphasizes the restoration of social relationships through a restorative justice approach, including within the military justice system. The research aims to analyze the implementation of restorative justice in military criminal cases adjudicated by the Madiun III-13 Military Court and to examine the legal considerations of the panel of judges in applying this approach in Decision Number 26-K/PM.III-13/AD/VII/2025 concerning fraud committed by a member of the Indonesian National Armed Forces (TNI). This study employs a normative legal research method using statutory and case-based approaches, supported by the analysis of judicial decisions and relevant empirical data related to military justice practices. The findings indicate that restorative justice was implemented through a mutual agreement between the perpetrator and the victim, accompanied by a mechanism for compensating the victim’s losses, while maintaining the principles of military discipline. Accordingly, restorative justice can be proportionally integrated into the military criminal justice system.